Search for production of heavy particles decaying to top quarks and invisible particles in pp collisions at √s = 1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We present a search for a new particle T' decaying to top quark via T' → t + X, where X is an invisible particle. In a data sample with 4.8  fb(-1) of integrated luminosity collected by the CDF II detector at Fermilab in pp collisions with √s = 1.96  TeV, we search for pair production of T' in the lepton + jets channel, pp → tt + X + X → ℓνbqq'b + X + X. We interpret our results primarily in terms of a model where T' are exotic fourth generation quarks and X are dark matter particles. Current direct and indirect bounds on such exotic quarks restrict their masses to be between 300 and 600  GeV/c2, the dark matter particle mass being anywhere below m(T'). The data are consistent with standard model expectations, and we set 95% confidence level limits on the generic production of T'T' → tt + X + X. For the dark matter model we exclude T' at 95% confidence level up to m(T') = 360  GeV/c2 for m(X) ≤ 100  GeV/c2.